Socioeconomic and proximate determinants of mortality in children under five years of age in Peru (2015-2018) - Paredes Mamani, Rene Paz (2020)
The objective of this study is to find the socioeconomic and proximate determinants of mortality in children under five years of age in Peru. To this end, the study focuses on the theoretical approach of  Mosley and Chen (1984) and employs the econometric methodology of the Cox semi-parametric and proportional hazards model and the Kaplan and Meier non-parametric model. With regard to socioeconomic determinants, the results show that the mother’s years of education, the household economic status, and the mother’s health coverage significantly reduce the risk of death for children under the age of five. Likewise, the mother’s years of education has a significant interaction effect with the household socioeconomic level and access to health service coverage, which influence child survival. As for the proximal determinants, the mother’s age, birth intervals, birth order, and health facilities all predict the risk of death for children under five years of age.